The effects of tacrolimus on the activity and expression of tissue factor in the rat ovary with ischemia-reperfusion induced injury - ALTURFAN, EBRU IŞIK; AK, KORAY (INST ANIMAL REPRODUCTION FOOD RESEARCH, 2015)
In the present study, the effects of tacrolimus on the activity and expression of tissue factor (TF) were investigated in the ovarian ischemia-reperfusion induced injury in rats. Twenty-eight female rats (8-12 weeks, 300-350 g) were divided into four groups: control, ischemia-reperfusion (IR), tacrolimus treated before ischemia (TBI), and tacrolimus treated before reperfusion (TBR) groups (n = 7/per group). TF activity was measured using Quick's method, whereas TF expression was examined immunohistochemically. TF activity was significantly higher in all treated groups compared with the control group. Strong ovarian TF expression was demonstrated in the IR and TBR groups. Moreover, tacrolimus decreased TF activity in the TBI group compared with the IR group. The decreased activity of TF in the ovarian IR model may prevent IR-related inflammation during transplant procedure. (C) 2015 Society for Biology of Reproduction & the Institute of Animal Reproduction and Food Research of Polish Academy of Sciences in Olsztyn. Published by Elsevier Sp. z.o.o. All rights reserved.
Keywords: Tacrolimus; Tissue factor; Ovary; Ischemia reperfusion; FACTOR PATHWAY INHIBITOR; COLI SEPTIC SHOCK; ISCHEMIA/REPERFUSION INJURY; KIDNEY-TRANSPLANTATION; FOLLOW-UP; BLOOD; IMMUNOSUPPRESSION; CRYOPRESERVATION; INFLAMMATION; MECHANISMS